2022
DOI: 10.1038/s41401-022-00876-9
|View full text |Cite
|
Sign up to set email alerts
|

Activating α7nAChR ameliorates abdominal aortic aneurysm through inhibiting pyroptosis mediated by NLRP3 inflammasome

Abstract: Abdominal aortic aneurysm (AAA) is defined as a dilated aorta in diameter at least 1.5 times of a normal aorta. Our previous studies found that activating α7 nicotinic acetylcholine receptor (α7nAChR) had a protective effect on vascular injury. This work was to investigate whether activating α7nAChR could influence AAA formation and explore its mechanisms. AAA models were established by angiotensin II (Ang II) infusion in ApoE−/− mice or in wild type and α7nAChR−/− mice. In vitro mouse aortic smooth muscle (MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, using α-BGT at the dose (1 μg/kg/d) did not reverse the inhibitory effects of DMXBA on the activation of microglia [ 184 ]. Deng et al showed that the activation of α7 nAChR could significantly inhibit the expression of NLRP3 inflammasome; this result was consistent with those of a study by Fu [ 201 , 202 ]. Furthermore, activating the α7 nAChR could also attenuate OS [ 216 ].…”
Section: Correlations Between Depression and Inflammation Based On α7...supporting
confidence: 84%
“…Interestingly, using α-BGT at the dose (1 μg/kg/d) did not reverse the inhibitory effects of DMXBA on the activation of microglia [ 184 ]. Deng et al showed that the activation of α7 nAChR could significantly inhibit the expression of NLRP3 inflammasome; this result was consistent with those of a study by Fu [ 201 , 202 ]. Furthermore, activating the α7 nAChR could also attenuate OS [ 216 ].…”
Section: Correlations Between Depression and Inflammation Based On α7...supporting
confidence: 84%
“…SNPs involving all the above-mentioned RAAS molecules, ( ACE/ACE2/AGT/AGTR1 ), while protective in malaria, have been implicated in severe adult COVID-19 outcomes (Table 2 ) [ 104 , 106 , 115 ]. Their net haplotype effect could significantly impact Ang II and EPO levels, eNOS activity, NO generation and bioavailability, perturbing NLRP3 inflammasome regulation, endothelial function, peripheral vascular resistance, and blood pressure (Table 2 ) [ 52 , 57 , 58 , 108 110 , 116 ].…”
Section: The No Genetic Pathway To Mis-cmentioning
confidence: 99%
“…6 B). PXDN has been previously suggested to catalyze hypochlorous acid (HOCL) generation in HO, which also markedly increases the ROS production and the inflammatory response [ 15 , 16 ]. PXDN is the new signal node mediating the phenotype change of VSMCs, which also has an important effect on AAA formation [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…This work acquired mouse aortic smooth muscle cells (MOVAS) in American Type Culture Collection (ATCC). For establishing the aneurysmal microenvironment within MOVAS, this work adopted TNF-α for stimulating MOVAS [ 15 , 16 ]. The MOVAS cell line was grown in DMEM media that contained 1% penicillin/streptomycin and 10% fetal bovine serum (FBS), followed by incubation under 5% CO2 and 37 °C conditions.…”
Section: Methodsmentioning
confidence: 99%